Llengua i identitat en l'obra de Benvingut Oliver i Joan Baptista Perales. - MARTÍ-BADIA, ADRIÀ (Scripta)
This paper analyses the reaction of the Valencian scholars Benvingut Oliver and Joan Baptista Perales against postulates on the Catalan Romance philology in the middle of the nineteenth century. Moreover, this work tries to relate Oliver and Perales position with others scholars and writers of the Renaixença Valenciana movement and the awareness of linguistic community shared with Catalan speakers from Catalonia, the Balearic Islands and North Catalonia. From the middle of the nineteenth century the German romanists found the Romance philology. They established µCatalan» as the name of the language of the Catalan-speaking areas. Even this is different from Occitan and has nothing to do with Limousin, which was known by this name since the early sixteenth century. Regarding the identity and the name of the Catalan language, these assumptions are quickly received and assumed in Catalonia. Although in the Balearic Islands and North Catalonia they were received positively with very few exceptions. Whereas in Valencia, only a minority of scholars like Benvingut Oliver and Joan B. Perales -among others- accepted and disseminated these postulates.